Comparative numerical and experimental analysis of thermal and hydraulic performance of improved plate fin heat sinks - Tariq, A. (Elsevier Ltd, 2021)
The benefits of multiple perforations and slots in a plate-fin heat sink are investigated using a conjugate heat transfer model and complementary experimentation. Heat transfer and pressure drop are analyzed across the two, novel plate-fin heat sinks (with perforations and slots). The experimental data validates the conjugate heat transfer CFD model for the air-cooled heat sink. The results from the CFD model show that novel plate-fin heat sinks tend to have a higher heat transfer coefficient than the plane fins without slots and perforations. Also, pressure drop of the novel plate-fin heat sinks is lower than the plane plate-fin heat sink, so less fan power is required for novel heat sinks. For a range of Re number 13,049 to 52195, on average novel plate-fin heat sink-1 (NPFHS-1) and novel plate-fin heat sink-2 (NPFHS-2) have 42.8 and 35.9 higher Nu number than that of the plane plate-fin heat sink (PPFHS). An additional advantage of the reduction in mass of heat sink is achieved because of slots and perforations. Â© 2020 Elsevier Ltd